An epidemic of the gastro-intestinal type of influenza in Port Lincoln, South Australia: 1905-1906 - Telford, Robert Whitson (The University of Edinburgh, 1909)
The occurrence of an Epidemic of Influenza where the cases exhibited, practicall7 symptoms characteristic of one variety of the disease in question, has seemed to me to be worthy of being brought before the notice of others, and I have embodied my experience in the form of a thesis for the degree of M.D. in my University.

I propose to place on record the symptoms and characters of the disease as met with at the bedside and then to endeavour to bring my observations into line with experiences already published in the literature.